Students' Pseudo-Thinking in Solving the Area of Obtuse Triangles: A Mindset-Based Perspective - Adhitya, Yusuf; Wahyudin, Wahyudin; Prabawanto, Sufyani (SEAMEO Regional Centre for QITEP in Mathematics, 2025)
The research aims to describe the different characteristics of students’ pseudo-thinking in solving areas of obtuse triangles based on their mindset. The categorization of pseudo-thinking is based on the Vinner and Subanji frameworks, while the mindset is categorized according to the Dweck framework. The research was conducted in one of the Junior High Schools in the Kebumen district with 111 students. The study employs a qualitative, grounded theory design. Data were collected through the math test, the mindset questionnaire, and the interview. The data were analyzed using a process that consists of open, axial, and selective coding to identify patterns of reasoning among students. The study found that students with a growth mindset exhibit both true and false pseudo-thinking, whereas students with a fixed mindset exhibit only true pseudo-thinking. Students with a growth mindset tend to engage in pseudo-thinking by misapplying the Pythagorean Theorem. On the other hand, fixed-mindset students often perform pseudo-thinking by using the incorrect formula. GMS is often overconfident in its old knowledge, leading to incorrect decisions, while FMS tends to focus solely on memorizing formulas and settings without reflection. This study is significant because it highlights how students’ mindsets influence their problem-solving abilities, particularly in geometric problems. Educators can use the insight gained from the study to develop effective learning strategies and help students grasp mathematics more deeply.